EFFECT OF DIFFERENT CRYOPROTECTANTS ON SPERM PLASMA MEMBRANE INTEGRITY OF OSMANABADI AND SIROHI BUCK SEMEN - DAGLI, N R; BAKSHI , S A; GULAWANE , S U; VANAGE , G (The Indian Journal of Animal Reproduction, 2023)
Semen was collected from six Osmanabadi and six Sirohi bucks weekly for six weeks by Artificial Vagina method. Semen was diluted using Tris Egg yolk Glycerol (TYG), Tris Egg yolk Ethylene Glycol (TYE) and Tris -Dimethyl sulphoxide (DMSO) dilutors (TYO) and evaluated for sperm plasma membrane integrity by HOS test at pre (S°C) and post freezing (-196°C at 24 and 72 hours) stage. At pre freezing (S°C) stage in Osmanabadi buck semen there was no significant difference (P>0.0S) across different dilutors with respect to HOS positive sperm percentage but in Sirohi bucks significantly higher sperm plasma membrane integrity was observed in TYO and TYG than TYE diluter. At 24 hours post freezing stage in Osmanabadi buck semen significantly higher plasma membrane integrity was noted in TYO than TYG am.I TYE dilutors. In Sirohi buck ::;ernen significantly higher plasma membrane integrity was noted in TYO than TYE diluter, TYG being intermediate. At 72 hrs post freezing stage in Osmanabadi bucks semen there was no significant difference (p>0.0S) across different dilutors with respect to HOS positive sperm percentage. In Sirohi bucks semen significantly, higher (P<0.0S) percentage of plasma membrane integrity was observed in TYO than TYE dilutors. It was concluded that in both the breeds higher plasma membrane integrity was observed in TYO diluter which indicates that DMSO was more effective cryoprotectant than ethylene glycol and glycerol in preserving sperm membrane integrity during cryopreservation of Osmanabadi and Sirohi bucks semen.